The Advantages and Barriers of Automation in Malaysia Construction Industry - Nik Fatma Arisya, Nik Yahya; Mazura, Mahdzir; Ho, Jack, Yong Jie (INTI International University, 2020)
Malaysian construction industry is still familiar with the conventional system and the technology that suits them well and therefore they are unwilling to switch to a modern construction system like Industrialised Building System (IBS). Conventional system always associates with low quality and productivity, high risk on worker’s safety, and excessive reliance on labors if the project adopting conventional system. Other than that, on site work normally involves extreme activities on the site that cause constant nuisances to local communities such as messy environment, traffic chaos, noise, and air pollution. The aim of this research is to encourage the implementation of automation in Malaysia construction industry. The objectives of this paper are; to identify the benefits of automation in construction industry, secondly, to identify the barriers on the implementation of automation works in construction industry and finally to recommend the implementation of automation which may improve the quality of workmanship. Questionnaire survey were conducted to collect the viewpoints among developers, contractors and manufacturers of IBS to ensure the richness of the data collected. Frequency analysis and Mean Score Indices were used to analyse the results. Results revealed that majority of the respondents agreed on the most critical barrier to the implementation of automation in Malaysian construction industry and they were not ready to move forward.